Efeitos do programa Agroamigo sobre os pequenos produtores rurais do Cariri cearense - Duarte, Silvia Patrícia da Silva (2017)
Given the relevance of family agriculture in the Brazilian context, as well as in the Northeast region, there is a need for studies that seek to analyze the policies aimed at the development of this activity. Therefore, the present study aimed to verify the impact of the Agroamigo Rural Microcredit Program on the production and productivity per worker of the beneficiary family farmers in the State of Ceará. The data analyzed were obtained from a field survey carried out in three municipalities that compose the Central Cariri from November to December 2016. For this, the observations of the sample were balanced by the Entropia method so that the control group Become more similar in order to generate more robust results. Propensity Score Matching (PSM) was then applied. From the results obtained, it was observed that in relation to the gross value of production, the beneficiaries of Agroamigo presented an average difference of R $ 490.65 in relation to non-beneficiaries. Regarding the gross value of production per worker, the data show to be insignificant and, therefore, no analysis can be made of the impact of the agroamigo on this variable. Thus, the results suggest that family farmers who receive credit, on average, have higher production value, as well as higher productivity, in relation to non-beneficiaries. Thus, the inclusion of family farmers in the credit market through Agroamigo has proven effective and serves as an example for new policies. Despite the limitations of the study, it is clear the participation and importance of the Program for the rural environment and its area of activity.